(untitled) (Global Journal of Human-Social Science, 2012)
The aim of this paper is to show that the Islamic finance is more stable than the conventional finance constituting thus a means to reduce the impact of financial crisis Using a VAR model for the financial indexes of France SBF250 United States DOW JONES United Kingdom FTSE100 Indonesia JAKISLM and Saudi Arabia TADAWUL covering the period 26 02 2007- 12 20 2010 we show that the effect of a shock on the American market during the period of crisis is negatively transmitted on all other markets but with a small extent on the market using the method of Islamic financing